THE DEVELOPMENT OF ENGLISH TEXTBOOK BY USING ADDIE-MODEL TO IMPROVE ENGLISH SPEAKING SKILL FOR NON-ENGLISH DEPARTMENT STUDENTS - Maitri Rahmadhani; Supriadi Supriadi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
A textbook is crucial in teaching-learning process at the university level. However, many textbooks in universities are lack in practice and too theoretical. This can be an obstacle for non-English department students. It will be hard for them to speak in English if the existing textbooks only concern in grammatical issues and put aside the communicative side (Speaking). This study aims to develop a practical and effective English textbook that prioritize the communicative side i.e., the spoken English for non-English department students. The research method used in this research is the Research & Development (R&D) by using the ADDIE development model in which the non-English Department students of STKIP Al Maksum Langkat as its research subject. The research sample was taken randomly (Random Sampling) based on the research needs. From the data taken, it was found that: 1) the developed-English textbook is declared very valid (92.9%) by 6 expert validators and could be used but needed minor revisions, 2) textbooks had met the criteria of practicality and effectiveness in improving the English speaking skill of non-English department students.